Engineering Metamaterial Interface Scattering Coefficients via Quantum Graph Theory - Lawrie, T.M.; Tanner, G.; Chaplain, G.J. (Acta Physica Polonica A, 2023)
For layered metamaterial devices, the reflection and transmission coefficients at an interface typically depend on the properties of the coupling between different layers. In this paper, we set out to engineer the reflection/transmission behaviour at boundaries to obtain desirable properties such as achieving total reflection and transmission. Based on the quantum graph formulation for modelling metamaterials developed in Sci. Rep. 12 (1), 18006 (2022), we tailor the interface reflection and transmission coefficients by patterning the boundary with resonant elements at each interface vertex. By tuning the internal lengths of the resonant elements, we demonstrate both minimization and maximization of the reflection coefficient via a scattering formulation. In addition, we present an interface set-up incorporating beyond-nearest-neighbour connections, which yields narrow-band transmission for certain angles only, creating an angular filtering interface.